2021
DOI: 10.1002/polq.13150
|View full text |Cite
|
Sign up to set email alerts
|

The President on Capitol Hill: A Theory of Institutional Influence

Abstract: reality is a social construction" (p. 14). In this reading, Derrida and Foucault paved the way for Breitbart and Hannity. It speaks strongly for the impact of ideas. Readers who take the title literally may wonder whether the bulk of a nation has "lost its mind," or whether it is only the 46 percent who chose a casino magnate. Patterson inspired me to look back a few years. In 2008, a contender with an African parent and an unusual name won with 9,549,105 votes to spare. Up again, his margin was still 4,984,10… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…Mechanical modeling of skeletal muscle was based on hill theory. Then, the kinematics data and inverse dynamics data are used for multibody dynamics modeling and analysis [ 7 ]. Finally, the static optimization method is used to estimate the muscle force, and the fusion analysis of the model is carried out.…”
Section: Methodsmentioning
confidence: 99%
“…Mechanical modeling of skeletal muscle was based on hill theory. Then, the kinematics data and inverse dynamics data are used for multibody dynamics modeling and analysis [ 7 ]. Finally, the static optimization method is used to estimate the muscle force, and the fusion analysis of the model is carried out.…”
Section: Methodsmentioning
confidence: 99%
“…A final event that occurred during the Trump presidency and that influenced Putin that he would likely not face a challenge from the us in the event of an invasion of Ukraine was the insurrection in Washington on January 6, 2021. It demonstrated that the us was weak, divided and collapsing politically (Liévano & Coe, 2021). More importantly, it suggested that the future president, Joe Biden, would have to focus most of his attention on domestic political, leaving little time for a coherent foreign policy.…”
Section: A Powerful and Threatening Alliancementioning
confidence: 99%
“…The instability usually has been the result of the excessive use of resources to fund global aspirations. In other words, Russia's history is replete with examples of imperial overstretch (Kennedy, 1987). Two examples are worth noting.…”
Section: Empire and Revengementioning
confidence: 99%